2022
DOI: 10.1096/fj.202201051r
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA UCA1 promotes the expression and function of P‐glycoprotein by sponging miR‐16‐5p in human placental BeWo cells

Abstract: Investigations on placental P‐glycoprotein (P‐gp) regulation could provide more therapeutic targets for individualized and safe pharmacotherapy during pregnancy. The role of long noncoding RNA (lncRNA) on placental P‐gp regulation is lacking. The present study was carried out to investigate the regulation and underlying mechanisms of lncRNA urothelial carcinoma associated 1 (UCA1) on P‐gp in Bewo cells. lncRNA UCA1 inhibition or overexpression could decrease or increase ABCB1 mRNA expression, P‐gp expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…ATP-binding cassette (ABC) transporters contribute dominantly to the drugs’ transplacental transportation, including p-glycoprotein, multiple drug-resistant protein, and breast cancer resistance protein. Several research studies demonstrated that the expression of ABC transporters is associated with the prevalence of cardiac birth defects ( Wang et al, 2013 ; Wang et al, 2014a ; Wang et al, 2014b ; Wang et al, 2015 ; Wang et al, 2021 ; Tang et al, 2023 ).…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 99%
“…ATP-binding cassette (ABC) transporters contribute dominantly to the drugs’ transplacental transportation, including p-glycoprotein, multiple drug-resistant protein, and breast cancer resistance protein. Several research studies demonstrated that the expression of ABC transporters is associated with the prevalence of cardiac birth defects ( Wang et al, 2013 ; Wang et al, 2014a ; Wang et al, 2014b ; Wang et al, 2015 ; Wang et al, 2021 ; Tang et al, 2023 ).…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 99%
“…Studies indicated that dysregulation of specific lncRNAs were linked with the occurrence, development, and metastasis of tumors. [30][31][32][33][34][35] Moreover, lncRNAs act as bridges to transmit information in tumor cells and tumor microenvironment. [36][37][38] For example, angiogenesis-related lncRNAs may be reliable in predicting the prognosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ATP-binding cassette family of placental e ux transporters contains a protein known as P-gp that is very expressed. Placental trophoblast P-gp can utilize ATP to restore GC in the maternal stream (Ge et al, 2021;Tang et al, 2023). Many studies on different animals including humans have revealed that DNA methylation of stress-related HPA axis genes is one potential epigenetic mechanism by which chronic stress may alter GC sensitivity (Florian Rakers ;Ji.…”
Section: Introductionmentioning
confidence: 99%